Analisis Faktor Kerusakan Bahan Pustaka di Perpustakaan SMP Negeri 4 Sungguminasa, Gowa - Salamah, St. Ummu (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2015)
The damaged of library collections must be concerned by all type of libraries. It always occured in library, particularly in school libraries. The study will investigate factors that damaged library collections and ways to solve such a case in the library of SMP 4 Sungguminasa, Gowa (a secondary school located in Gowa, South Sulawesi). The data were gathred through direct observations and interviews with staf in the library. The study found that there were kinds of damaged of library collection, which were 1) caused by studens, 2) caused by floods, and 3) caused by insects. In terms of its preservation, the library have some solutions which were 1) determining strict penalties for the library users who have damaged the collections, 2) binding library materials, 3) setting the library room, 4) maka a report to the school authoritative to care of library school, 5) cleaning routinely the library shelves.